1996
DOI: 10.1093/hmg/5.8.1179
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel sarcoglycan gene at 5q33 encoding a sarcolemmal 35 kDa glycoprotein

Abstract: Mutations in any of the genes encoding the alpha, beta or gamma-sarcoglycan components of dystrophin-associated glycoproteins result in both sporadic and familial cases of either limb-girdle muscular dystrophy or severe childhood autosomal recessive muscular dystrophy. The collective name 'sarcoglycanopathies' has been proposed for these forms. We report the identification of a fourth member of the human sarcoglycan family. We named this novel cDNA delta-sarcoglycan. Its mRNA expression is abundant in striated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
83
2
4

Year Published

1997
1997
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(91 citation statements)
references
References 38 publications
1
83
2
4
Order By: Relevance
“…The authors suggested that this d-SG mutation has a dominant negative effect. 10 All together, these data suggest that mutation in d-SG gene is likely to be responsible for the DCM, and muscle weakness could result from potential deleterious synergic effect on muscle function of b-and d-SG mutations. We, like others, found that clinical phenotypes of patients with primary sarcoglycanopathy are heterogeneous and cover a clinical spectrum that is similar to the one resulting from mutations in the DMD gene, though Duchenne-and Becker-like muscular dystrophy are the most frequent phenotypes.…”
Section: Sarcoglycan Gene Mutations M Trabelsi Et Almentioning
confidence: 83%
“…The authors suggested that this d-SG mutation has a dominant negative effect. 10 All together, these data suggest that mutation in d-SG gene is likely to be responsible for the DCM, and muscle weakness could result from potential deleterious synergic effect on muscle function of b-and d-SG mutations. We, like others, found that clinical phenotypes of patients with primary sarcoglycanopathy are heterogeneous and cover a clinical spectrum that is similar to the one resulting from mutations in the DMD gene, though Duchenne-and Becker-like muscular dystrophy are the most frequent phenotypes.…”
Section: Sarcoglycan Gene Mutations M Trabelsi Et Almentioning
confidence: 83%
“…After secondary antibodies incubations, cells were washed with PBS and then fixed for 15 minutes with 4% paraformaldehyde in PBS (PFA). For immunofluorescence analysis, cells were fixed with 4% PFA, washed with 50 mmol/L NH 4 Cl, and then permeabilized with 0.5% Triton X-100. Permeabilized cells were then probed with the selected antibodies as above described.…”
Section: Confocal Immunofluorescence Analysis Of Cellsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] Mutations in four genes encoding sarcoglycan proteins (␣-, ␤-, ␥-and ␦-SG) are responsible for various forms of autosomal recessive limb-girdle muscular dystrophy (LGMD 2D, 2E, 2C and 2F, respectively). [9][10][11][12][13][14][15][16] This heterogeneous group of diseases nevertheless shares a common feature in that a primary deficiency of any of the sarcoglycan proteins leads to the reduction or the absence of all other members of the SG-SSPN complex. 17 In non-consanguineous populations, ␣-sarcoglycan deficiency is the most frequent cause of autosomal recessive LGMD with a sarcoglycan defect (sarcoglycanopathy).…”
Section: Introductionmentioning
confidence: 99%